Intelligence Quotient Levels and Sub Tests Comparison in Autistic Children - Sah, Vijay Kumar; Rimal, Hem Sagar; Rimal, Archana (Journal of Nobel Medical College, 2016)
Background Autism spectrum disorders (ASD) are disorders of neurodevelopmental origin characterized by social reciprocity deficits, communication deficits, and unusual restricted and repetitive behaviors. In some of these people, measured IQ (Intelligence Quotient) can be normal or even superior or low.Material and Methods This is a Retrospective study in autistic children. We have analyzed with autistic disorder, 47 patients had savant skills and 1 patients of MR (Mental Retardation) had savant skills. China- Wechsler Young Children Scale of Intelligence (C-WYCSI) and China-Wechsler Intelligence Scale for Children(C-WISC) were used for calculating IQ levels in different age groups.Results Asperger’s syndrome (AS) children had higher verbal IQ (VIQ) and full scale IQ (FSIQ) compared to autism and high functional autism (HFA) children with statistical difference. Autism children had lower VIQ, performance IQ and FSIQ compared to HFA and AS children with statistical significance. AS children had higher values in C-WISC and CWYCSI compared to autism children.Conclusion Children with Asperger’s syndrome have higher full IQ and Sub test IQ compared with autism and HFA children.Journal of Nobel Medical College Volume 5, Number 1, Issue 8, January-July 2016, 9-13